3D printing of mineral–polymer bone substitutes based on sodium alginate and calcium phosphate - Egorov, Aleksey A.; Fedotov, Alexander Yu.; Mironov, Anton V.; Komlev, Vladimir S.; Popov, Vladimir K.; Zobkov, Yury V. (Beilstein Journal of Nanotechnology, 2016)
We demonstrate a relatively simple route for three-dimensional (3D) printing of complex-shaped biocompatible structures based on sodium alginate and calcium phosphate (CP) for bone tissue engineering. The fabrication of 3D composite structures was performed through the synthesis of inorganic particles within a biopolymer macromolecular network during 3D printing process. The formation of a new CP phase was studied through X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. Both the phase composition and the diameter of the CP particles depend on the concentration of a liquid component (i.e., the “ink”). The 3D printed structures were fabricated and found to have large interconnected porous systems (mean diameter ≈800 μm) and were found to possess compressive strengths from 0.45 to 1.0 MPa. This new approach can be effectively applied for fabrication of biocompatible scaffolds for bone tissue engineering constructions.
Keywords: 3D printing; bone graft; calcium phosphate; composite materials; sodium alginate; tissue engineering